Indirect treatment comparison of lurbinectedin versus other second-line treatments for small-cell lung cancer - Raj Hanvesakul; Badri Rengarajan; Navit Naveh; Anne Boccuti; Julie E Park; Adekemi Adeyemi; Clyde Caisip; Jeroen P Jansen; Florence R Wilson (Journal of Comparative Effectiveness Research, 2023)
Aim: Compare lurbinectedin versus other second-line (2L) small-cell lung cancer (SCLC) treatments. Methods: An unanchored matching-adjusted indirect comparison connected the platinum-sensitive SCLC cohort of a single-arm lurbinectedin trial to a network of three randomized controlled trials (oral and intravenous [IV] topotecan, and platinum re-challenge) identified by systematic literature review. Network meta-analysis methods estimated relative treatment effects. Results: In platinum-sensitive patients, lurbinectedin demonstrated a survival benefit and favorable safety profile versus oral and IV topotecan and platinum re-challenge (overall survival, hazard ratio [HR]: 0.43; 95% credible interval [CrI]: 0.27, 0.67; HR: 0.43; 95% CrI: 0.26, 0.70; HR: 0.42; 95% CrI: 0.30, 0.58 respectively). Conclusion: Lurbinectedin showed a robust survival benefit and favorable safety versus other SCLC treatments in 2L platinum-sensitive SCLC.